Chiral 3d–4f Clusters with NIR-III Magneto-Optical Activity Driven by Lanthanide f–f Transition - Jia-Nan Chen; Fu-Li Sun; Xing Wang; Ming-Qiang Qi; Ya-Xuan Xue; Gui-Lin Zhuang; La-Sheng Long; Lan-Sun Zheng; Xiang-Jian Kong (Journal of the American Chemical Society, 2026)
Abstract Chiral molecular materials with strong magneto-optical responses in the near-infrared III (NIR-III, 1600–2500 nm) region are attractive for applications in photonics, biomedicine, and advanced optical materials, but molecular magneto-optical phenomena in this spectral window remain largely unexplored. Here, we report six pairs of chiral 3d–4f molecular clusters, R/S-Ln3Mn4 and R/S-Ln12Mn12 (Ln = HoIII, TbIII, and YIII), and systematically investigate their chiroptical and magneto-optical properties in the NIR-III region. Circular dichroism (CD) and magnetic circular dichroism (MCD) spectroscopy reveal that R/S-Ho3Mn4 and R/S-Ho12Mn12 clusters exhibit pronounced CD and MCD responses in the NIR-III region arising from long-wavelength HoIII f–f transitions, whereas R/S-Tb3Mn4 and R/S-Tb12Mn12 show strong MCD responses but no resolved CD signals. These findings identify long-wavelength lanthanide f–f transitions as the origin of the NIR-III chiroptical and magneto-optical activity. Notably, the R/S-Ln12Mn12 series exhibits larger gMCD values and stronger NIR-III MCD responses than the corresponding R/S-Ln3Mn4 analogues. This enhancement may arise from the change in local LnIII coordination geometry from D4d in Ln3Mn4 to D2d in Ln12Mn12, which favors a stronger Zeeman-perturbed MCD response, along with cooperative LnIII-MnII weak magnetic interactions in Ln12Mn12. This work provides the first molecular example of f–f-transition-driven chiroptical and magneto-optical activity across the NIR-III window and establishes chiral 3d–4f clusters as structurally defined platforms for tuning long-wavelength magneto-optical responses.